Identification of novel antiviral host factors by functional gene expression analysis using in vitro HBV infection assay systems. - Takuto Nosaka; Tatsushi Naito; Yu Akazawa; Kazuto Takahashi; Hidetaka Matsuda; Masahiro Ohtani; Tsutomu Nishizawa; Hiroaki Okamoto; Yasunari Nakamoto (PLoS ONE)
To cure hepatitis B virus (HBV) infection, it is essential to elucidate the function of hepatocyte host factors in regulating the viral life cycle. Signaling and transcription activator of transcription (STAT)1 play important roles in immune responses, but STAT1-independent pathways have also been shown to have important biological reactivity. Using an in vitro HBV infection assay system, the current study aimed to investigate the STAT1-independent host factors that contribute to the control of viral infection by comprehensive functional screening. The in vitro HBV infection system was established using primary human hepatocytes (PXB cells) infected with HBV derived from a plasmid containing the 1.3-mer HBV genome. Comprehensive functional studies were performed using small interfering RNA (siRNA) and vector transfection and analyzed using microarrays. Knockdown of STAT1 increased viral products in HBV-transfected HepG2 cells, but decreased in HBV-infected PXB cells. RNA microarray was performed using HBV-infected PXB cells with STAT1 knockdown. Fumarylacetoacetate hydrolase (FAH) was extracted by siRNA of genes in PXB cells altered by STAT1 knockdown. Transfection of FAH inhibited HBV replication. Dimethyl fumarate (DMF), the methyl ester of FAH metabolite, showed antiviral effects by inducing autophagy and anti-HBV-related genes. Independently of STAT1, FAH was identified as a host factor that contributes to the control of viral infection, and its metabolite, DMF, exhibited antiviral activity. These results suggest that the novel host factor FAH and its metabolites may be an innovative therapeutic strategy to control the HBV life cycle.